Adult Relationships in Multiple Contexts and Associations With Adolescent Mental Health. (October 2016) - Capp, Gordon; Berkowitz, Ruth; Sullivan, Kathrine; Astor, Ron Avi; De Pedro, Kris; Gilreath, Tamika D.; Benbenishty, Rami; Rice, Eric
Purpose: Adult relationships provide critical support for adolescents because of their potential to foster positive development and provide protective influences. Few studies examine multiple ecological layers of adult relationships in connection with well-being and depression. This study examines the influence of relationships from multiple contexts for adolescents and their mental health. Method: Data from the 2011 California Healthy Kids Survey was used for this analysis; a sample of 7th-, 9th-, and 11th-grade students ( N = 14, 931) was drawn from 6 school districts in Southern California. Results: Regression analyses revealed that parent, teacher, and community adult support were all significantly positively associated with well-being and significantly negatively associated with depression. Discussion: Social support explained more variance in well-being than in depression, indicating that adult support may be more important for supporting well-being. This study supports the belief that individual categories and combinations of adult support are important.